Calcific Aortic Valve Stenosis with Aging and Current Development in its Pathophysiology - Kodra, Arber; Kim, Michael (International Journal of Angiology, 2022)
Aortic stenosis is the most common valvular heart disease affecting the elderly. While most patients have a prolonged asymptomatic phase, the development of symptoms ushers in a phase clinical deterioration that often leads to sudden death without an intervention. Treatment of aortic stenosis with valve replacement often relieves the symptoms but still leaves behind a remodeled left ventricle which may not recover. Understanding the pathophysiology of aortic stenosis and realizing that the disease process may be a more active biological entity rather than a passive degenerative process will help us prevent it. This review serves to summarize the latest literature on the pathophysiology of aortic stenosis in the elderly.
Keywords: advanced glycosylation end product; aortic valve disease; atherosclerosis; biomarkers; valvular heart disease; cardiovascular risk factors